Silicon-perovskite combinational solar cells degradation phenomena for futuristic IOTs powering - Pratibha Giri; J. P. Tiwari (Discover Applied Sciences)
Abstract Internet of Things (IoTs) nodes are presently powered through primary and secondary batteries, which face the issue of recharging and replacing within a limited life span of a battery. Hence, scientists and researchers are searching for alternative powering sources or supporting powering by default battery power. Organic or perovskite solar cells (OSCs/PSCs) are presented as an alternative to powering the IoT nodes. Another option for powering IoT nodes may be based on silicon-perovskite combinational heterojunction solar cells, which may be better concerning OSCs/PSCs as the stability issue of OSCs/PSCs, which is hampering the commercialization as a powering source for IoT nodes. Herein, the case of degradation of the silicon-perovskite combinational heterojunction solar cells of structure Al/Si/MAPbI3/Ag having device parameters such as Voc ~ 0.41 ± 0.05, Jsc ~ 3.93 ± 0.05, FF ~ 66.56 ± 0.05 and efficiency ~ 1.08 ± 0.05 will be presented in an ambient environment and the sunshine in November 2021 for ~ 97 h in the capital city of India New Delhi. The T80 for the device tested in the background under sunlight exposure is ~ 4 h only, concerning five days in indoor testing conditions. The degradation observation of silicon-perovskite combinational heterojunction solar cells shows an all-characteristic parameter decay with respect to degradation in indoor lab conditions, which is only fill factor (FF) driven degradation. The degradation is analyzed through XRD, SEM, PL, and EDAX studies of degraded and fresh devices.